A COMPARATIVE STUDY OF SUSTAINABLE DEVELOPMENT IN SMALL AND MEDIUM TOURIST HOTEL INDUSTRY FROM PIERIA (GREECE) AND TAIWAN - Anestis K. Fotiadis; Chris Vassiliadis (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2015)
This paper is exploring the relationship of the small hotel sector with the principles of sustainable tourism development. Main objective is to highlight the benefits expected to accrue to the hotel industry and examine the degree of awareness among owners of small and medium hotel units on issues related to sustainable tourism development. A questionnaire was distributed in Greece and Taiwan and a logit model was used, to examine the impact of the dichotomous dependent variable of nationality between Taiwanese and Greek SME hoteliers. Greeks and Taiwanese have remarkable differences on how they perceive sustainable tourism development and what impact that kind of development will have on their enterprises. Greeks seems to be much more optimistic than Taiwanese when it comes to environmental issues. For Greeks high investment costs are the most important reason for not implementing the adoption of sustainable development. The biggest problem for Taiwanese hoteliers is the lack of trained staff.